Desempenho de variedades de mamoeiro em clima subtropical do Estado de São Paulo - Silva, Marcelo de Souza [UNESP] (2016)
There is little information regarding the productive performance of papaya varieties in different soil and climatic conditions. In this way, evaluation of this fruit plant in different regions is very important for its development. This work aimed to assess the phenology, production and fruit quality of papaya varieties under subtropical condition of São Paulo State. The experiment was conducted at Universidade Estadual Paulista (UNESP), College of Agricultural Sciences, Campus of Botucatu, SP - Lageado Farm. It was evaluated Sunrise Solo variety, Tainung n°. 1 hybrid and Comum variety. The experimental design was a randomized block with six replications and five plants per plot. The phenological data were obtained by counting the number of days regarding the different phenological phases of the plants. It was determined the stem diameter, plant height, insertion height of the first flowers, as well as percentage of male, female and hermaphrodite flowers at flowering. It was also obtained the fruit growth curve, accumulation of degree-days regarding the different phenological phases, number and percentage of normal fruits, pentandric and carpelloid. It was also evaluated the productive characteristics of the plant, as well as physical and physicochemical quality of different fruit varieties. Based on the results, it was possible to infer that the pentandria and carpeloidia of the percentages of both papaya varieties studied are less than to 10% tolerated for culture. The growth curves of the fruit of variety Sunrise soil and Tainung n° 1 hybrid behave sigmoidal shape and stabilize the growth to 120 days after anthesis. The average productivity of the Sunrise Solo, Comum and Tainung n° 1 varieties under the conditions of the city of Botucatu – SP are 28.6 t ha-1, 8.0 t ha-1 and 40.5 t ha-1, respectively. Chemically, the fruits of the Tainung n° 1 hybrid meet the consumer market due to higher values of soluble solids, "Ratio" (SS/AT) and technological index.